1990
DOI: 10.1113/jphysiol.1990.sp017978
|View full text |Cite
|
Sign up to set email alerts
|

The physiological basis of the minimally distinct border demonstrated in the ganglion cells of the macaque retina.

Abstract: SUMMARY1. The minimally distinct border method involves setting the relative radiances of two adjacent, differently coloured fields until the border between them is minimally distinct. At these radiance settings, the two fields are found to be of equal luminance. The task shares with flicker photometry all the requirements of a photometric method.2. We have recorded responses of macaque ganglion cells to such borders moved back and forth across the receptive field; the size of the luminance step across the bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 47 publications
2
63
0
Order By: Relevance
“…We have shown that cells of the MC-pathway display properties consistent with their being the substrate of the MDB task (Kaiser, Lee, Martin & Valberg, 1990). On adjusting the luminance contrast across a border between two different colours, activity in the MC-pathway goes through a minimum when the colours are at equal luminance.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…We have shown that cells of the MC-pathway display properties consistent with their being the substrate of the MDB task (Kaiser, Lee, Martin & Valberg, 1990). On adjusting the luminance contrast across a border between two different colours, activity in the MC-pathway goes through a minimum when the colours are at equal luminance.…”
Section: Introductionmentioning
confidence: 91%
“…End-tidal PIto was kept near 4 % by adjusting the rate and depth of ventilation, and body temperature was maintained near 37-5 'C. Further details of the experimental procedulre are giveen in Kaiser et al (1990) and details of recording technique and cell classification are to be founid in Lee, Martin & Valberg (1989b). WTe recorded from ganglion cells from parafoveal retina.…”
Section: Methodsmentioning
confidence: 99%
“…The change in photometric sensitivity is specific to methods that employ temporal modulation. Though MC-pathway mediation has been inferred for both flicker photometric 14 and minimally distinct border 15 (MDB) photometric matches, MDB matches between middle and long wavelength lights do not show the sizable reduction in long wavelength sensitivity with increasing light level seen with flicker photometric matches. 16 Recordings from parvocellular pathway cells revealed no systematic response patterns consistent with human psychophysical data and are not reported here.…”
Section: Introductionmentioning
confidence: 99%
“…Although M-cells are generally thought to possess broad-band spectral sensitivity, there are two ways by which they convey information about chromatic contrast. First, individual M-cells signal the presence of chromatic contrast in isoluminant patterns without regard for chromatic contrast polarity (Schiller and Colby, 1983;Lee et al, 1988Lee et al, , 1989aKaiser et al, 1990;Logothetis et al, 1990;Valberg et al, 1992;Dacey, 1996). Second, because isoluminant points vary across the population of M-cells, some cells will transmit a signal for any heterochromatic luminance ratio selected (Logothetis et al, 1990).…”
Section: Abstract: Luminance; Chrominance; Magnocellular; Parvocellumentioning
confidence: 99%